Redek vzrok Cushingovega sindroma - Zemljič, Eva (Medicinski razgledi, 2002)
Cushing's syndrome is the term used to describe clinical symptoms and signs related to an increased concentration of glucocorticoids in the body. Cushing's syndrome can be divided into two categories: corticotropin-dependent Cushing's syndrome, in which abnormally high plasma corticotropin levels stimulate the adrenal cortex to produce excessive amounts of glucocorticoids, and corticotropin-independent Cushing's syndrome, in which excessive production of glucocortioids is due to abnormal adrenocortical tissue. In rare cases, the cause of Cushing's syndrome may be an ectopic tumor which secretes corticotropin. The main clinical symptoms of ectopic Cushing's syndrome include high blood pressure, edema, hypokalemia and glucose intolerance. Ectopic corticotropin production is most commonly found in pulmonary small cell carcinoma and rarely in carcinoid tumors, islet cell carcinoma of the pancreas, thymoma and medullary thyroid carcinoma. Treatment of ectopic Cushing's syndrome is initially symptomatic; when the cause of the syndrome has been established, it can be etiologic.
Keywords: Cushing syndrome; Cushingov sindrom; Etiologija; Etiology; ACTH sindrom, ektopični; ACTH syndrome, ectopic; diagnostika; endokrinologija